Developing Academic Achievement on Self-Conduct in accordance with Buddhist Principles for 2nd Level of Secondary Education Students: A Case Study Teaching of Banmoh Pattananukul School - Panichayapan, Panadda; Chanklan, Phiraphat; Khamkom, Thanchanok (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This research aims to create learning activity plans for the topic of self-conduct according to Buddhist principles by using the case method, to study students’ achievement, and to evaluate student satisfaction after implementing the case method. The sample group, derived by purposive sampling, included 42 students of Mathayom 2 who enrolled in semester 1/2023 at Banmoh Pattananukul School, Saraburi Province. Research instruments included 12 learning plans, a 30-question multiple-choice academic achievement test, and a 20-item 5-likert scale satisfaction survey. Statistics used in this research were average, standard deviation, and dependent t-test. Research results revealed that 12 learning plans were developed, and the comparison of academic achievement yielded the post-test was higher than that of the pre-test at the statistically significant level of .05. For the result of the satisfaction survey after implementing the case method, students were satisfied at the highest level ( = 4.64).